Using incentives to improve performance of extension services in Rwanda - Kinyua, Henry; Lion, Karin; Agarwal, Shreya (Digital Green, 2019)
The Feed the Future Developing Local Extension Capacity (DLEC), in partnership with One Acre Fund and the Rwanda Agriculture Board, is investigating the impact of providing incentives to farmer promoters at national scale. Acting as role model farmers, they are the first point of contact for Rwandan farmers with the goal of improving productivity by increasing adoption of good agricultural practices and access to improved inputs. Farmer promoters establish village demonstration plots to showcase good agricultural practices and their impact on yield, train farmers, and support the implementation of the government’s subsidy system through marketing of inputs.